A novel adduct of ECG fused to piceid and four new dimeric stilbene glycosides from Polygonum cuspidatum. Issue 65 (23rd June 2016) - Yang, Ya-nan; Li, Fu-shuang; Liu, Fu; Feng, Zi-ming; Jiang, Jian-shuang; Zhang, Pei-cheng
Abstract : Polyflavanostilbene B (1 ), an unusual adduct of epicatechin-3- O -gallate fused to piceid through a carbon–carbon bond, four new dimeric stilbene glycosides (2–5 ), and four new compounds (6–9 ), were isolated from the rhizome of Polygonum cuspidatum . Abstract : Polyflavanostilbene B (1 ), an unusual adduct of epicatechin-3- O -gallate fused to piceid through a carbon–carbon bond, four new dimeric stilbene glycosides (2–5 ), three new stilbene glucosides (6–8 ), one new flavan glucoside (9 ), and six known compounds were isolated from the rhizome of Polygonum cuspidatum . The structures of these compounds were elucidated using spectroscopic data, including electronic circular dichroism (ECD) and Rh2 (OCOCF3 )4 -induced CD spectra. All of the compounds were screened for their inhibitory activity against α-glucosidase using acarbose as a positive control (IC50 = 385 μM), and strong inhibitory activity against α-glucosidase was observed for compound8 (IC50 = 3.04 μM).